2005
DOI: 10.1592/phco.2005.25.8.1035
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Morbidity Associated with Nonadherence to Statin Therapy

Abstract: A detectable excess of cardiovascular morbidity appears to be associated with nonadherence to statin therapy. Our analysis suggests that many occurrences of myocardial infarction could be prevented with improvements in adherence. Larger studies are necessary to determine the association between adherence and other cardiovascular end points.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(60 citation statements)
references
References 27 publications
2
54
0
4
Order By: Relevance
“…The statin class of medications was selected for analysis because adherence to these medications is known to be poor, 6,9-12 and our research group has experience with statin adherence analyses using Saskatchewan health data. 7,10 Community Pharmacy Selection Community pharmacy companies that provide service to the urban centers in Saskatchewan were subjectively grouped into I n Canada, most prescription medications are dispensed by licensed pharmacists through community pharmacies. Because of their frequent contact with patients, it has been suggested that community pharmacists are in an ideal position to identify and improve medication nonadherence.…”
Section: Subject Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The statin class of medications was selected for analysis because adherence to these medications is known to be poor, 6,9-12 and our research group has experience with statin adherence analyses using Saskatchewan health data. 7,10 Community Pharmacy Selection Community pharmacy companies that provide service to the urban centers in Saskatchewan were subjectively grouped into I n Canada, most prescription medications are dispensed by licensed pharmacists through community pharmacies. Because of their frequent contact with patients, it has been suggested that community pharmacists are in an ideal position to identify and improve medication nonadherence.…”
Section: Subject Selectionmentioning
confidence: 99%
“…4 Medication nonadherence is a global problem and is a predictor of negative patient outcomes. [5][6][7] Although many studies…”
Section: Subject Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonadherence to diabetes medications as well as statin therapy has been demonstrated to result in adverse outcomes, including myocardial infarction, excess hospitalizations, and mortality. 3,21 Medication adherence that results in just a 1% reduction in HbA1c can lead to a 37% reduction in microvascular complications and a 42% risk reduction in diabetes-related death. [22][23][24] Although our study resulted in a 0.5% further reduction in HbA1c for the OPCS group compared with the usual care group, 61% of the OPCS group had a 1% or more reduction in HbA1c, compared with 52% of the usual care group (P = 0.008).…”
Section: ■■ Discussionmentioning
confidence: 99%
“…There is strong international evidence that cost influences adherence (Goldman et al 2007). A wealth of literature demonstrates the adverse effects of prescription drug non-adherence, such as increased emergency room visits, morbidities and mortalities (Blackburn et al 2005;Heisler et al 2010;Mojtabai and Olfson 2003;Tamblyn et al 2001). The heavy reliance of Canada' s universal health insurance coverage system on private prescription drug plans also means that significant use of cost-shifting mechanisms may have important equity implications.…”
Section: Discussionmentioning
confidence: 99%